Interview: Papillon contact radiotherapy: past, present and future. (December 2013) - Myint, Arthur Sun
Professor Arthur Sun Myint * speaks to Natasha Galukande, Commissioning Editor: Arthur Sun Myint graduated from the Institute of Medicine, Mingaladon, Burma in 1972 and came to the UK in 1977. He was appointed as a Clinical Scientist for the Medical Research Council Neutron trial project in 1983 and chaired the colorectal subgroup for neutron trials until 1995. He is now the Lead Clinician in papillon radiotherapy at the Clatterbridge Cancer Centre (Merseyside, UK) where he has worked as a consultant for nearly 25 years. His main research interest is in the treatment of rectal cancers and he introduced contact radiotherapy (Papillon) into the UK and started treating patients at The Clatterbridge Cancer Centre in 1993. So far, he has treated over 700 patients using the Papillon technique, which is the world's largest cohort of patients. He is a founder member of the International Contact Radiotherapy Society (ICONE) and he was appointed specialist advisor for NICE for rectal brachytherapy and helped to write the guidelines published in December 2006. He also serves as an advisor to NCRI rectal and anal subgroups, has published over 50 peer-reviewed publications and is the author of four text book chapters. He has served on the council of the Association of Coloproctology and the council of the Royal College of Radiologists. He was appointed to chair the GEC–ESTRO brachytherapy group for rectal and anal cancers in 2011. He is the contact radiotherapy course director at the Clatterbridge Cancer Centre and he has organized the next course on 9–10 October 2014. He was awarded a Honorary Professor in Gastroenterology by the University of Liverpool in December 2012.